INVESTIGATION OF CONCEPTUAL UNDERSTANDINGS OF PRE-SCHOOL AGE CHILDREN ON LIVING AND NON-LIVING THINGS - Ümit DEMİRAL (International Journal of Eurasia Social Sciences, 2018)
The aim of this study is to investigate the conceptual understanding of pre-school children on the living and non-living concepts along with the sources of these conceptual understandings. A descriptive pattern, which included quantitative and qualitative together, has been used in the study. The study group has been identified within the scope of the maximum variation sampling method, which is a type of purposive sampling. The study was conducted with 80 children aged between 4-6 years, who study in a pre-school institution located in Kırşehir. Living/Non-living things cards and interview questions were used as a data collection tool in the study. When the answers given by the children during the interviews were examined, it has been found that the conceptual understanding of living and non-living things is gathered in four categories; no conception, misconception, misunderstanding and correct understanding. Some of the children in the low-level of knowledge group were able to answer the names of the things they saw in the pictures partly. Based on the results of the study, it has been proposed to create educational environments that allow teachers, families and the media to convey existing concepts in a way that it will form correct meaning for the child which in turn will ensure the conceptual understanding of pre-school children.